Incidence of erectile dysfunction among middle-aged and aging sexual minority men living with or without HIV - Mustapha, Aishat; Polanka, Brittanny M.; Maini, Mansi; Ware, Deanna P.; Li, Xiuhong; Hart, Trevor A.; Brown, Todd; Palella, Frank; Gorbach, Pamina M.; Ho, Ken; Plankey, Michael (Frontiers in Public Health, 2024)
Erectile dysfunction (ED) has been established as a comorbidity among men living with HIV, but comparisons by HIV serostatus of ED incidence in a longitudinally followed up cohort of men are lacking. We sought to evaluate the incidence of ED across 12 years in a longitudinal cohort of sexual minority men (SMM) living with and without HIV. We analyzed ED incidence data for 625 participants in the longitudinal Multicenter AIDS Cohort Study from visits spanning October 2006 to April 2019. SMM living with HIV were more likely to have incident ED compared with those living without HIV (rate ratio: 1.41; 95% CI: 1.14-1.75). Older age, current diabetes, cumulative cigarette use, and cumulative antidepressant use were associated with increased incidence of ED in the entire sample.Self-identifying as Hispanic, current diabetes, and cumulative antidepressant use were positively associated with ED incidence among SMM living with HIV. Cumulative cigarette use was positively associated with greater ED incidence only among SMM living without HIV. In summary, age (full sample/with HIV), current diabetes (full sample/with HIV), cumulative cigarette use (full sample/ without HIV), and cumulative antidepressant use (full sample/with HIV) were associated with increased ED incidence. Skillful management of diabetes and careful titration of antidepressants along with smoking cessation practices are recommended to mitigate ED in this population.